EXAMINING THE CAUSAL NEXUS BETWEEN TOURIST ARRIVALS AND TERRORISM IN EMERGING COUNTRIES - Sinem Eyüboğlu; Kemal Eyuboglu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Theaim of the paper is to analyze the causal nexus between tourist arrivals andterrorism. In this paper, unlike other studies, we used the Global TerrorismIndex (GTI) prepared by the Institute for Economics & Peace for thedetermination of terrorism level of a country. For more unbiased and robustestimates, Dumitrescu and Hurlin (2012) method is employed to examine the causalnexus between tourist arrivals and terrorism in thirteen emerging countries coverthe period 2006-2016. The results indicated that there is a one-way causalityrunning from terrorism to tourist arrivals. Results suggest that emergingcountry authorities should increase security precautions to ensure thattourists feel safe and in order to attract more tourists, ceteris paribus.